The yin-yang of immunity: Immune dysregulation in myelodysplastic syndrome with different risk stratification - Peng, Xiaohuan; Zhu, Xiaofeng; Di, Tianning; Tang, Futian; Guo, Xiaojia; Liu, Yang; Bai, Jun; Li, Yanhong; Li, Lijuan; Zhang, Liansheng (Frontiers in Immunology, 2022)
Myelodysplastic syndrome (MDS) is a heterogeneous group of myeloid clonal diseases with diverse clinical courses, and immune dysregulation plays an important role in the pathogenesis of MDS. However, immune dysregulation is complex and heterogeneous in the development of MDS. The lower-risk MDS (LR-MDS) is mainly characterized by immune hyperfunction and increased apoptosis, and the immunosuppressive therapy induces a good response. Instead, higher-risk MDS (HR-MDS) is characterized by immune suppression and immune escape, and the immune activation therapy may improve the survival of HR-MDS. Furthermore, the immune dysregulation of some MDS changes dynamically which is characterized by the coexistence and mutual transformation of immune hyperfunction and immune suppression. Taken together, the authors think that the immune dysregulation in MDS with different risk stratification can be summarized by an advanced philosophical thought "Yin-Yang theory" in ancient China, meaning that the opposing forces may actually be interdependent and interconvertible. Clarifying the mechanism of immune dysregulation in MDS with different risk stratification can provide the new basis for the diagnosis and clinical treatment. This review focuses on the manifestations and roles of immune dysregulation in the different risk MDS, and summarizes the latest progress of immunotherapy in MDS.